Identity of the tree-spider crab, Parasesarma leptosoma (Hilgendorf, 1869 (Decapoda: Brachyura: Sesarmidae), with descriptions of seven new species from the Western Pacific - Li, Jheng-Jhang; Rahayu, Dwi Listyo; Ng, Peter K. L. (Zootaxa, 2018)
The identity of the tree-spider crab, Parasesarma leptosoma (Hilgendorf, 1869) (family Sesarmidae), which is believed to be widely distributed in the Indo-West Pacific, is reassessed and shown to be a species-complex with nine species, seven of which are here described as new. Parasesarma leptosoma sensu stricto is now restricted to South and East Africa; and P. limbense (Rathbun, 1914) from Sulawesi, which had been regarded as a junior synonym, is here recognized as a valid species. The following species are described as new: P. gecko n. sp. from Vanuatu, Fiji, Guam and Japan; P. macaco n. sp. from Taiwan and the Philippines; P. kui n. sp. from Taiwan; P. parvulum n. sp. from the Philippines; P. gracilipes n. sp. from Indonesian Papua; P. purpureum n. sp. from Malaysia; and P. tarantula n. sp. from Sulawesi, Indonesia. The nine species of the Parasesarma leptosoma species-complex can be separated by the different shapes of their carapaces, the form of the dactylar tubercles on the male chelipeds, proportions of their ambulatory legs and the structure of the male first gonopod.